Post-Traumatic Diaphragmatic Hernia Presenting as Bowel Obstruction 12 Years After a Chest Gunshot Wound: A Rare Delayed Diagnosis - Papa Mamadou Faye; Ulrich Igor Mbessoh Kengne; Ousmane Thiam; Mouhamadou Laye Diop; Joël Gabin Konlack Mekontso; Mouhamed Moustapha Gueye; Seydy Ly; Amacoumba Fall; Mame Dieme Diop; Christophe Mbueda; Naomi Makam; Alpha Oumar Toure; et al. (Case Reports in Surgery)
Post-traumatic diaphragmatic hernia (PTDH) is defined as the migration of intra-abdominal organs into the chest through a pathological defect in the diaphragm caused by trauma. PTDH is a rare condition, occurring in 3%–7% of all thoracoabdominal injuries. Approximately 14.6% of PTDH cases present months to years after the initial trauma. Cases of delayed PTDH complicated by bowel obstruction and perforation are exceedingly uncommon, with a reported prevalence of 0.17%–6%. In Africa, fewer than 10 cases of delayed PTDH have been documented over the past three decades. Despite the availability of published reports, there are no established practice guidelines for managing PTDH. Here, we present a case of delayed PTDH that manifested as acute bowel obstruction 12 years after a gunshot wound to the chest. The condition led to a fatal postoperative outcome. This case highlights the critical need for clinicians to consider PTDH in patients with a history of trauma presenting with acute bowel obstruction and underscores the importance of urgent surgical management to prevent fatal complications.